2007
DOI: 10.2488/jwrs.53.72
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Pilodyn for Estimating Basic Density and Its Applicability to Density-based Classifying of Cryptomeria japonica Green Logs

Abstract: We used a Pilodyn for estimating basic density in the green condition for the purpose of classifying logs of Cryptomeria japonica D. Don based on their density. The relationships between Pilodyn penetration depth in the radial direction Pr and basic density of blocks with pin penetration were examined in a wide basic density range of hardwoods and softwoods 199 779 kg/m 3 , and C. japonica 221 474 kg/m 3 . There were signifi cant negative correlations in hardwoods r 0.92, P 0.001 , softwoods r 0.86, P 0.001 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The average moisture content in the aqueous and underground sections was 171% and 180%, respectively [16]. A comparison between the penetration depth of this study and the values reported in previous studies suggested that the cedar logs collected in this study were almost sound [28,29]. The split surfaces of the log were observed by SEM to investigate the microbial presence and microstructure inside the log (Fig.…”
Section: Evaluation Of Soundness Of the Logs And Sem Observation Of The Cell Wall Surfacesupporting
confidence: 55%
“…The average moisture content in the aqueous and underground sections was 171% and 180%, respectively [16]. A comparison between the penetration depth of this study and the values reported in previous studies suggested that the cedar logs collected in this study were almost sound [28,29]. The split surfaces of the log were observed by SEM to investigate the microbial presence and microstructure inside the log (Fig.…”
Section: Evaluation Of Soundness Of the Logs And Sem Observation Of The Cell Wall Surfacesupporting
confidence: 55%
“…Pilodyn penetration is used as an indirect measurement of wood density in many species [19,20,22,23,25,43]. In our research, Pilodyn had a strong genetic correlation with wood density, which resulted in a high efficiency of indirect selection using Pilodyn targeting wood density.…”
Section: Discussionmentioning
confidence: 94%
“…The direct measurement of wood density is costly, so several indirect estimation methods are utilized, such as the Pilodyn penetration depth, which has a negative correlation with wood density [19][20][21][22]. A genetic correlation of wood density and Pilodyn penetration depth has also been reported for several species [23][24][25], but not yet for L. kaempferi.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between PP and either heartwood density or disc density was, nevertheless, moderately high. Several studies reported a high correlation between PP and wood density (Cown 1978;Taylor 1981;Hall 1988;Yamashita et al 2007;Fig. 3 Genetic gain in wood density by the direct selection and by the indirect selection using the Pilodyn.…”
Section: Discussionmentioning
confidence: 97%
“…Hall (1988) reported correlation coefficients between the Pilodyn results and wood density of -0.48 in Picea mariana, -0.62 in Picea glauca and -0.48 in Larix laricina. In Japanese species, Yamashita et al (2007) reported a correlation coefficient of -0.82 between penetration depth and the wood density of wood blocks from Cryptomeria japonica. Based on family means, the correlation coefficients are -0.79 in Cryptomeria japonica and -0.78 in Larix kaempferi (Fukatsu et al 2007).…”
Section: Introductionmentioning
confidence: 97%